2008
DOI: 10.1179/174892409x427931
|View full text |Cite
|
Sign up to set email alerts
|

Development of membranes for hydrogen separation: Pd coated V–10Pd

Abstract: Numerous Group IVB and VB alloys were prepared and tested as potential membrane materials but most of these materials were brittle or exhibited cracking during hydrogen exposure. One of the more ductile alloys, V -lOPd (at. %), was fabricated into a thin 5 (avg. of three different samples) at 400°C, which is slightly higher than the permeability of Pd-23Ag at that temperature. A 1400 h hydrogen flux test at 400°C demonstrated that the rate of metallic interdiffusion was slow between the V -lOPd foil and the l0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Operating temperatures above 350 ° C are therefore extremely desirable to mitigate this problem. [ 9 ] These two issues combine to severely constrain the temperature window in which BCC metals may be effectively employed for H 2 separation.…”
Section: Doi: 101002/adma201100931mentioning
confidence: 99%
“…Operating temperatures above 350 ° C are therefore extremely desirable to mitigate this problem. [ 9 ] These two issues combine to severely constrain the temperature window in which BCC metals may be effectively employed for H 2 separation.…”
Section: Doi: 101002/adma201100931mentioning
confidence: 99%
“…At temperatures below 350 C hydrogen embrittlement can occur, causing these membranes to break [17,18]. Hydrogen embrittlement at low temperature is thought to be due to the increase solubility of hydrogen in each of the BCC metals at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen permeation flux of Pd/V/Pd and Pd/Ve8Ni/Pd membranes were approximately 11.25 and 12.25 ml min À1 cm À2 at 673 K, which are equivalent to the permeability of 1.76 Â 10 À8 and 1.96 Â 10 À8 mol$ m À1 s À1 Pa À0.5 , respectively. The hydrogen permeability of V and 91Ve9Ni alloy membranes at 673 K was reported as 3.0 Â 10 À7 [19] and 8.5 Â 10 À8 mol m À1 s À1 Pa À0.5 [15], respectively [11]. Although the hydrogen permeability of Pdcoated V-based membranes tested in this study was lower than the ones reported in the past studies [15,19], both Pd/V/Pd and Pd/Ve8Ni/Pd membranes maintained good performances even at 573 K.…”
Section: Hydrogen Permeation Flux Of V-based Membranesmentioning
confidence: 99%